1993
DOI: 10.1007/bf00019945
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a spinach gene responsive to low temperature and water stress

Abstract: The characterization of a cDNA for an 85 kDa spinach protein, CAP85 (cold acclimation protein) that is responsive to cold acclimation and water stress is described. Both transcript and protein levels are increased during cold acclimation and water stress. A novel characteristic of CAP85 is the presence of an 11 amino acid, lysine-rich repeat, common to Group 2 LEAs (late embryogenesis abundant proteins), which is included within a larger repeating motif present in 11 copies. Two other motifs of 8 and 16 residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
89
0
1

Year Published

1995
1995
2008
2008

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 62 publications
9
89
0
1
Order By: Relevance
“…Most group 2 LEA/Rab/dehydrin proteins possess only two lysine-rich repeats. The cold-induced spinach CAPS85 protein [23] and the wheat COR39 protein [24] contain 11 and six lysine-rich repeats, respectively. Both proteins lack the serine stretch but COR39 possesses a glycine-rich sequence that is repeated six times.…”
Section: Resultsmentioning
confidence: 99%
“…Most group 2 LEA/Rab/dehydrin proteins possess only two lysine-rich repeats. The cold-induced spinach CAPS85 protein [23] and the wheat COR39 protein [24] contain 11 and six lysine-rich repeats, respectively. Both proteins lack the serine stretch but COR39 possesses a glycine-rich sequence that is repeated six times.…”
Section: Resultsmentioning
confidence: 99%
“…DHNs localize primarily to the nucleus or cytoplasm (Houde et al, 1995;Bracale et al, 1997), but studies also corroborate their presence either in the plasma membrane (Danyluk et al, 1998), endoplasmic reticulum (Neven et al, 1993), chloroplast (Wisniewski et al, 1999), mitochondria (Borovskii et al, 2002) or even in the vacuole (Heyen et al, 2002). DHNs may thus be expressed either constitutively [e.g.…”
Section: Structure and Functional Studies Of Dhnamentioning
confidence: 87%
“…In some studies antibodies have been used to examine the expression (Lin and Thomashow, 1992a;Neven et al, 1993;Kazuoka and Oeda, 1994;Boothe et al, 1995;Houde et al, 1995) and to determine the cytological location (Lin and Thomashow, 1992a;Neven et al, 1993;Houde et al, 1995) of low-temperature-induced proteins. In only a few cases have low-temperature-induced proteins been purified (Kazuoka and Oeda, 1994;Houde et al, 1995;Gilmour et al, 1996) and no detailed structural analyses of these proteins have as yet been reported to our knowledge.…”
mentioning
confidence: 99%
“…A common feature among many low-temperatureinduced proteins is their tendency to remain soluble following boiling (Lin et al, 1990;Lin and Thomashow, 1992a;Neven et al, 1993). This property is a reflection of the fact that these proteins are extremely hydrophilic, which is also shared by many dehydration-induced proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation